Application of English Teaching Methods in Nursing: Comparison of Learning Outcomes Before and After Midterm Exam - Wim Ukhrowi (Indo Publishing, 2026)
ESP constitutes a vital component of the nursing education curriculum, as healthcare professionals are required to engage in cross-cultural communication, comprehend international medical literature, and prepare accurate and standardized nursing care documentation. Students’ success in acquiring these competencies is highly dependent on the relevance and effectiveness of the instructional methods implemented during the learning process. This study aims to describe the teaching methods employed in Nursing English before and after the midterm examination, and to compare student learning outcomes based on midterm and final examination scores. A mixed-methods research design utilizing an explanatory sequential model was adopted, involving 35 fourth-year undergraduate nursing students at the Faculty of Nursing, Unipdu Jombang. Qualitative data regarding instructional methods were obtained through learning process records, while quantitative data were derived from student academic achievement documents. Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The findings reveal a notable shift in teaching approaches: from theory-oriented instruction and translation exercises prior to the midterm examination to practice-based learning, clinical simulations, and role-playing activities thereafter. Quantitatively, the average score improved from 78.80 at the midterm stage to 83.11 in the final assessment. Statistical analysis confirmed a significant difference with a p-value < 0.05. In conclusion, the transition from conventional teaching strategies to an approach centered on clinical requirements and practical application proved effective in enhancing academic performance. Instructional methods specifically tailored to the professional context of nursing were found to be more effective in promoting students’ comprehension and mastery of English language competencies.